Low temperature fabrication of lead-free piezoelectric KNLNTS ceramics by the solid state combustion technique. (3rd October 2017) - Mathrmool, Krailas; Udeye, Thanya; Bongkarn, Theerachai
ABSTRACT: In this study, lead-free (K0.44 Na0.52 Li0.04 )(Nb0.84 Ta0.10 Sb0.06 )O3 KNLNTS ceramics were synthesized by the solid state combustion technique. A pure perovskite phase was found in the powders calcined at 650°C which was lower than the calcined temperature of a conventional solid state reaction technique by ∼200 °C. All calcined (600–800°C) powders consisted of a relatively spherical morphology, with particle powders compacted to a large agglomerated form. The average particle size was approximately 130 nm, obtained from the powders calcined at 650°C. A pure perovskite phase was found in all sintered (1000–1150°C) samples. The structure of the samples composed of orthorhombic and tetragonal phase. At high sintering temperature (1150°C), the structure was mixed with cubic phase. The microstructure exhibited square and rectangular shapes and the average grain size was (0.76–2.32 µm) and increased with an increasing of the sintering temperatures. The densest ceramic (4.42 g/cm 3 ), the highest permittivity (ϵr at Tc ∼6114), good ferroelectric properties ( Pr ∼30.63 µC/cm 2 and Ec ∼8.56 kV/cm) and piezoelectric constant ( d33 ) of 203 pC/N were obtained by the sample sintered at 1100°C.